The ferredoxin/thioredoxin system: from discovery to molecular structures and beyond. - Buchanan, Bob B. (2002)
Experiments initiated in the early 1960s on fermentative bacteria led to the discovery of ferredoxin-dependent alpha-ketocarboxylation reactions that were later found to be key to a new cycle for the assimilation of carbon dioxide in photosynthetic bacteria (the reductive carboxylic acid or reverse citric cycle). The latter finding set the stage for the discovery of a regulatory system, the ferredoxin/thioredoxin system, functional in photosynthesis in chloroplasts and oxygen-evolving photosynthetic prokaryotes. The chloroplast research led to a description of the extraplastidic NADP/thioredoxin system that is now known to function in heterotrophic plant processes such as seed germination and self-incompatibility. Extensions of the fundamental research have begun to open doors to the broad application of thioredoxin in technology and medicine.